Figure, image, reputation of politicians in the language and the actual political discourse (a corpus research experience): Образ, имидж, репутация политика в языке и актуальном политическом дискурсе (опыт корпусного исследования) - Severskaya, Olga; Saakyan, Levon (Przegląd Wschodnioeuropejski, 2020)
The purpose of the article is to show the evolution of the concepts of “figure”, “image” and “reputation” in the Russian language in the last fifty years, to analyze their use in modern political discourse. The corpus study on the material of modern political journalism, showed that “image”, the emotionally affecting perception of a person, does not always coincide with the “figure” as the type or character associated with the speaker. Content-analysis of the use of lexemes imidzh, obraz, reputatsiya showed that in the semantic plan they influenced each other, becoming synonyms in various meanings. The semantic evolution of the word imidzh went from an impression of appearance to stereotypical ideas that can be appreciated by society. The “figure”, judging by the Russian National Corpus data, today looks more like a “role” in a film or a play, responding to the theatricalization of the political process. An analysis of the speeches of the president, the prime minister of the country, regional rulers, deputies, and opposition leaders reveals the “masks” of the Grate-Powerman and Patriot, People’s Chosen, Ordinary Man, Strong Man (Powerful Hand), Debater, Distressor, and some others, used as an element of a discursive strategy.